Mathematical economics an integrated approach - Rowcroft, John E. (Prentice Hall Canada Inc., 1994)
This is a book on economic analysis using mathematical techniques. The emphasis of the book is on translating a verbal economic problem into the appropriate mathematical terms, solving it, and expressing the solution in the economic context of the original problem